Mesoporous Caged‐γ‐AlOOH‐Double‐Stranded RNA Analog Complexes for Cancer Immunotherapy. Issue 1 (4th December 2017) - Li, Xia; Shenashen, Mohamed A.; Wang, Xiupeng; Ito, Atsuo; Taniguchi, Akiyoshi; EI‐Safty, Sherif A.
Abstract: Alum exhibits the superior biocompatibility in the history of human healthcare, as the only FDA‐approved inorganic adjuvant in most human vaccines. However, up to now, there are few reports about the in‐depth research between its nanostructure and carrier properties in vitro and in vivo. In this study, the caged architecture of uniform mesoporous γ‐AlOOH nanorods (MANRs) comprises realigned pores and open windows at the edges, 1D tubular tunnels, and oxyhydroxide layer that can serve as carriers for cancer immunotherapy. Compared with commercial alum, the MANRs exhibit a higher loading amount of a model cancer antigen and a stronger intracellular uptake by THP‐1‐differentiated macrophage‐like cells in vitro. Compared with commercial alum and soluble ovalbumin, the MANRs loaded with a model cancer antigen, ovalbumi, and an immunopotentiator, double‐stranded RNA analog poly(I:C) markedly increase the anticancer immunity and CD4+ and CD8+ T cell populations in mouse splenocytes in vivo. The MANRs are promising as an adjuvant substance in cancer immunotherapy for clinical use. Abstract : The caged architecture of uniform mesoporous γ‐AlOOH nanorods is successfully fabricated as carriers for cancer immunotherapy. Compared with commercial alum, the MANRs exhibit a high loading amount of a model cancer antigen, a strong intracellular uptake by antigen presenting cells, and a remarkable increase in the anticancer immunity and CD4 + and CD8 + T‐cell populations in mouse splenocytes in vivo.